Improving self-monitoring of text comprehension: Effects of generic and adaptive feedback - Braumann, Sophia Elena Edith (Utrecht University, 2024)
This dissertation presents seven studies, organised into four empirical chapters, addressing the general research question on whether different types of feedback can boost an existing diagramming intervention to further improve students’ monitoring accuracy of their own text comprehension. The following research question is addressed first: Do generic diagram standards as feedback (with or without explicit self-scoring instructions) improve monitoring accuracy and text comprehension? More specifically, Chapter 2 and 3 report on studies that focus on improving young adult learners’ (Chapter 2), and secondary school students’ (Chapter 3) monitoring accuracy and text comprehension through standards. Chapter 2 presents two studies. The first study experimentally investigates whether the effect of providing diagram standards as feedback during immediate diagramming would further improve monitoring accuracy and text comprehension. The second study used process measures (eye tracking and verbal reporting) to investigate how students use the standard, whether they are aware of the quality of their answers and whether they use this information (i.e., those cues) for their monitoring judgements. The two studies in Chapter 3 address the added value of combining diagram standards and self-scoring instructions during delayed (Experiment 1) and immediate (Experiment 2) diagramming. The studies in Chapter 4 and 5 investigate the research question: Does individually adapted feedback via diagram-nudges (Chapter 4) or individually adapted feedback on diagramming performance and monitoring judgements (Chapter 5) improve monitoring and regulation accuracy? In Chapter 4, two studies are presented. In the first study, it is investigated whether nudging by means of visually highlighting diagram boxes would improve adult learners’ identification of correct, incorrect, and empty diagram boxes. Also, their awareness and perceived usefulness of the nudges are investigated both quantitatively and qualitatively in this study (Experiment 1). In the second study, it is investigated whether individually adapted feedback on students’ commission errors, by means of nudging with and without communicating (i.e., telling) the meaning of the nudges to students (i.e., Please attend to the incorrectly completed boxes, while visually signalling incorrectly completed boxes) can improve monitoring accuracy. Nudging feedback (with or without telling instructions) is compared to generic feedback standards or receiving no feedback (with or without preceding diagramming) for improving secondary school students’ monitoring accuracy (Experiment 2). Chapter 5 reports on an experimental study that focuses on individually adapted feedback during diagramming on both performance (by marking empty or incorrectly completed diagram boxes) and monitoring judgements (by informing students which JOL score would be expected based on their diagramming performance) to further improve secondary school students’ monitoring accuracy. In addition, the studies in Chapters 3 and 5 investigated whether the (expected) effect of the interventions on monitoring accuracy would also transfer to new text comprehension tasks on which feedback was no longer provided. Chapter 6 provides a summary and general discussion of the main findings and (potential) implications for educational practice and directions for future research.
Keywords: Monitoring accuracy; text comprehension; regulation accuracy; self-regulated learning; causal diagramming; feedback standards; self-scoring instructions; transfer; nudging; automated response evaluation